PROPOLIS, THE ALTERNATIVE NATURAL MATERIAL FOR SEX REVERSAL IN TILAPIA - Didik Ariyanto; Adam Robisalmi; Alien Karlina Larasati (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2012)
Growth of tilapia male is better than female. Practically, cultured of all male population are more efficient than that of mixed sex population. Sex reversal with 17-methyltestosterone hormone is the most popular technique to make all or nearly all male tilapia. But, alternative substitution materials for sex reversal must be found due to limited application of this synthetic hormone that caused of its carcinogenic potential on human body. Besides that, 17-methyltestosterones are also suspected as the unfriendly material for environment. Several early studies were conducted to find the alternative materials for sex reversal in tilapia. One of the highly potential material found is aromatase inhibitors, the materials which are function to inhibit the secretion of aromatase, the catalyst enzyme in the bio-synthetic of estrogen from androgen. Due to the chemical characteristic materials and relatively high price of aromatase inhibitor, we tried to find the natural material which has similar composition or function to that compound. One of the natural suspected materials which has similar function with aromatase inhibitors is propolis. Chrysin as apart of flavonoid compound found in the propolis shows the most potent inhibitors of aromatase. Early study showed that application of propolis up to 3 mL.kg-1 of feed resulted the highest percentage of male in tilapia. Based on that study, the optimum dosage of propolis for sex reverse of the tilapia has not been known. This study was conducted to know the optimum dosage of a commercial propolis for sex reversal in tilapia, especially in NIFI red tilapia. The dosages proposed in this study were 3, 4, 5 and 6 mL propolis.kg-1 of feed. Sex reversal was carried out in aquarium for 35 days. Rearing of fingerling fish for 2 months was conducted in hapas suspended in earthen pond. The result showed that application of 5 mL propolis.kg-1 of feed resulted the highest proportion of male, which up to 76.67%. Application of all propolis dosages in this study did not affect to the survival rate and the abnormality of fish.